Teacher Leaders’ Strategies in Implementing Deep Learning within the Merdeka Curriculum: A Multi-Case Study in Islamic Primary Schools - Khofifah, Eva Nur; Mislikhah, St; Usriyah, Lailatul (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The Merdeka Curriculum promotes deep learning to cultivate meaningful understanding, critical thinking, and 21st-century competencies among students. However, its implementation in Islamic primary schools (madrasahs) remains challenging due to limited resources, teacher readiness, and contextual constraints. This study explores the strategies employed by Teacher Leaders (Guru Penggerak) in implementing deep learning within two madrasahs: MI Raudhatul Jannah Jenggawah and MI Al Barokah Annur Jember. Using a qualitative phenomenological approach, six teacher leaders (three from each school) participated in in-depth interviews, classroom observations, and documentation analysis. The findings indicate that teacher leaders initially encountered misconceptions and anxiety regarding deep learning, often equating it with technology integration. Over time, they adopted adaptive strategies such as project-based learning, reflective questioning, simple learning media, and integrating cultural and family experiences into classroom activities. Despite challenges such as limited digital facilities, time constraints, and occasional parental resistance, these strategies fostered greater student engagement and active participation. The study underscores the pivotal role of teacher leaders as change agents who bridge the gap between curriculum ideals and classroom realities. Contextual, resource-sensitive strategies and sustained professional development are essential to ensure the effective and sustainable implementation of deep learning in madrasah settings.